2014
DOI: 10.1080/10942912.2014.900786
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Grape Pomace on the Quality of Silver Carp(Hypophthalmichthys molitrix)Fillets During Refrigerated Storage

Abstract: This study aimed to determine the phenolic content and antioxidant effect of grape pomace extract on silver carp fillets during refrigerated storage. Total phenolic content of grape pomace extract was quantified by colorimetric methods. Silver carp samples were treated with 0, 2, and 4% of grape pomace extract (g extract/100 g flesh) and stored 15 days in a refrigerator (4 • C). Changes in pH, peroxide value, thiobarbituric acid, and heme iron at 0, 3, 6, 9, 12, and 15 days of storage were investigated. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The seasoning was effective at inhibiting the growth of TAMB, LAB, and Enterobacteriaceae, considerably increasing the shelf‐life. Similar results have recently been pointed out by Hasani and Alizadeh (), however, in this case, the effect was less relevant than in other studies. Other researchers showed that low concentrations of grape extracts (lower than 0.2%) had no effect on the final population or only produced slightly lower final counts of TAMB (Garrido and others ; Kumar and others ).…”
Section: Functions In the Food Industrysupporting
confidence: 91%
See 2 more Smart Citations
“…The seasoning was effective at inhibiting the growth of TAMB, LAB, and Enterobacteriaceae, considerably increasing the shelf‐life. Similar results have recently been pointed out by Hasani and Alizadeh (), however, in this case, the effect was less relevant than in other studies. Other researchers showed that low concentrations of grape extracts (lower than 0.2%) had no effect on the final population or only produced slightly lower final counts of TAMB (Garrido and others ; Kumar and others ).…”
Section: Functions In the Food Industrysupporting
confidence: 91%
“…Regarding concentration, relatively low levels of wine pomace extracts are required to achieve an antioxidant effect, although the published data vary depending on the type of product in use. So, different wine pomace products have been effective from levels as low as 10 ppm up to levels as high as 10% (Rojas and Brewer ; Shirahigue and others ; Hasani and Alizadeh ). Generally, a low health risk of prooxidant activities has been described, which facilitates the application of these products as antioxidants.…”
Section: Functions In the Food Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…At present, limited information on effects of grape seed proanthocyanidins on aquatic animals is available. There are only a few experimental reports on proanthocyanidins in rainbow trout (Oncorhynchus mykiss) (Kesbiç & Yigit, 2019), greenlip abalone (Haliotis laevigata) (Shiel et al, 2017), silver carp (Hypophthalmichthys molitrix) (Hasani & Alizadeh, 2015) and tilapia (Oreochromis niloticus) (Zhai et al, 2014). Nevertheless, the use of grape seed proanthocyanidins to stimulate disease resistance and promote the growth performance in sturgeons has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed significant antimicrobial activity of rosemary extract, reducing counts of Bacillus cereus/thuringiensis and Citrobacter freundii which dominated the microbiota of the controls. Hasani et al [ 72 ] reported that pomace extract significantly delayed psychrotrophic bacterial growth as well as TVC and TVB-N of refrigerated silver carp. Maghami et al [ 73 ] investigated the effect of chitosan nanoparticles (CNPs) loaded with fennel essential oil (FEO) in combination with MAP on microbial, chemical and sensorial properties of Huso huso fish fillets during refrigerated storage.…”
Section: Innovative Seafood Preservation Methodsmentioning
confidence: 99%